Enhancement of a simple user authentication scheme for grid computing - Ramamoorthy, Viknesh (2008)
Grid computing means a multiple independent computing, because it is composed of resource nodes not located within a single administrative domain. The goal of grid is to only provide secure grid service resources to legal users. Even though grid computing is more than just a technology to abet high performance computing, it is still have some issues to concerns and cares. One of the issues is security issues. Authentication is important part in grid security. Other process in grid are depends on authentication. The aim of this project is to enhance the method of password based authentication scheme and to get better password based authentication scheme in grid computing environment through its time complexity. In this project, the study is done on the existing grid security infrastructure and existing password based authentication scheme. Password Enable Certificate Free Grid Security Infrastructure (PECF-GSI) and A Simple User Authentication Scheme has been selected as the reference for the enhanced authentication scheme. Comparative study and pre-lab testing on A Simple User Authentication Scheme and PECF-GSI has been done in the research methodology. Finally, the enhanced authentication scheme has been designed, developed and tested based on four time complexity notations that are time for modular multiplication, time for multiplication of a number and an elliptic curve point, time for hashing operation and time for inversion. This project has achieved the aim, the scope and the objectives of the project by showing a good performance in terms of time complexity.